Falta de associação entre o polimorfismo genético do FTO, AKT1 e AKTIP e o sobrepeso e a obesidade infantis - Pereira, Patrícia de Araújo; Alvim-Soares, António Marcos; Sandrim, Valéria Cristina [UNESP]; Lanna, Carla Márcia Moreira; Souza-Costa, Débora Cristine; Belo, Vanessa de Almeida; de Paula, Jonas Jardim; Tanus-Santos, José Eduardo; Romano-Silva, Marco Aurélio; Miranda, Débora Marques de (Elsevier, 2016)
Objective Obesity is a chronic disease caused by both environmental and genetic factors. Epidemiological studies have documented that increased energy intake and sedentary lifestyle, as well as a genetic contribution, are forces behind the obesity epidemic. Knowledge about the interaction between genetic and environmental components can facilitate the choice of the most effective and specific measures for the prevention of obesity. The aim of this study was to assess the association between the FTO, AKT1, and AKTIP genes and childhood obesity and insulin resistance. Methods This was a case–control study in which SNPs in the FTO (rs99396096), AKT1, and AKTIP genes were genotyped in groups of controls and obese/overweight children. The study included 195 obese/overweight children and 153 control subjects. Results As expected, the obese/overweight group subjects had higher body mass index, higher fasting glucose, HOMA-IR index, total cholesterol, low-density lipoprotein, and triglycerides. However, no significant differences were observed in genes polymorphisms genotype or allele frequencies. Conclusion The present results suggest that AKT1, FTO, and AKTIP polymorphisms were not associated with obesity/overweight in Brazilians children. Future studies on the genetics of obesity in Brazilian children and their environment interactions are needed.
Lack of association between genetic polymorphism of FTO, AKT1 and AKTIP in childhood overweight and obesity
Keywords: AKT1; AKTIP; Childhood obesity; Fat mass and obesity associated; Gene; Single-nucleotide polymorphisms